Implementation of BMC-based teaching and learning factory model in increasing student competencies in leather creative skills concentration and imitation in vocational school - Cucu Sutianah; Meita Annisa Nurhutami; Alfian Azhar Yamin (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2023)
Learning in vocational education must be carried out with collaboration between educators, vocational schools, curriculum alignment, and learning in factories as miniature industries stakeholders to achieve assessment in the form of real assessment so that the achievement of learning objectives follows the needs of students and the world of work. Assessment in the form of assessment must be measured in real terms, with religious, character, moral, and cultural education values and work competencies following community expectations. The objectives to be achieved through this research are to produce a learning program that can improve student competence in Vocational High School (VHS), including identifying the current condition of learning implementation, obtaining learning planning findings, obtaining learning implementation findings, obtaining findings regarding the assessment of learning outcomes, identifying supporting and inhibiting factors, knowing students' perceptions of the implementation of the BMC-based teaching and learning factory model in improving student competence in the concentration of leather and imitation craft design and production expertise in VHS. With the implementation of a learning system using a block system as a teaching and learning factory, the implementation of learning must stimulate students to be more active in improving social skills, emotional skills, spiritual skills, scientific skills, mental skills, kinesthetic skills, as well as entrepreneurial skills, work ethics and safety, and work safety and the environment, which in turn can improve the competence and entrepreneurial character of students, following the vision and mission of the education unit.